Analisis Manfaat Penggunaan QRIS (Quick Response Indonesia Standart) Bagi Pedagang dan Pembeli dalam Pembayaran Non Tunai pada Bisnis UMKM: Studi Kasus pada UMKM Kel. Durian Kota Tebing Tinggi - Roza, Fitra Maulana; Nawawi, Zuhrinal M.; Syarvina, Wahyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The digital transformation in payment systems has encouraged micro, small, and medium enterprises (MSMEs) to adapt to technology, one of which is through the implementation of QRIS (Quick Response Code Indonesian Standard). This study aims to analyze the perceptions of MSME actors and consumers regarding the ease and benefits of using QRIS, identify the obstacles in its implementation, and evaluate its contribution to business efficiency and the independence of the national financial system. This research employed a descriptive qualitative method by conducting interviews with five informants, consisting of three MSME owners and two university students in Kelurahan Durian, Tebing Tinggi City. The results show that QRIS is perceived as a practical, fast, and secure payment method. Its use facilitates financial record-keeping for business owners and increases customer trust. The obstacles encountered are mostly technical, such as network issues and device limitations, but do not reduce users’ interest. Furthermore, QRIS contributes to maintaining domestic cash flow and reducing dependence on foreign payment systems, thus supporting national economic sovereignty. Overall, QRIS has proven effective as an inclusive digital payment solution for both MSMEs and consumers.